Implementasi Penagihan Pajak Dengan Surat Paksa Dan Penyitaan Dalam Upaya Optimalisasi Penerimaan Pajak Di Kantor Pelayanan Pajak Pratama Binjai - Sitepu, Kartika Dewanty; Marlina, Marlina; Leviza, Jelly (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
This article discusses the Implementation of Forced Tax Collection and Confiscation in an Effort to Optimize Tax Receipts at the Binjai Pratama Tax Office. Answering these problems used normative and empirical juridical research methods. The data used are primary data and secondary data. Field studies by conducting interviews with informants namely Bailiffs and Taxpayers. Data analysis was carried out qualitatively. From the results of the study showed that the implementation of tax collection with forced letters and seizures carried out by the Bailiff at the Binjai Primary Tax Service Office had been carried out in optimizing tax revenue. In reality, there are still some obstacles, namely the low compliance of taxpayers paying taxes, the address of registered taxpayers is difficult to find, the lack of supporting data, the number of bailiffs, and legislation. To overcome these obstacles, socialization and outreach activities to the public are carried out intensively and continuously, improving the address of registered taxpayers, adding bailiffs and human resources, increasing cooperation with third parties and clarifying the laws and regulations on active billing actions in order to achieve targets and realize tax revenues.